Congress “The Role of Diagnostic Complex and X-ray Endovascular Technologies at the Hospital Stage of Emergency and Acute Medical Care”, combined with the 19th Interregional Scientific and Practical Conference with International Participation “ Actual Issues of Diagnostic and Interventional Radiology and Surgical Technologies” (Vladikavkaz, June 27–29, 2019) - Article Editorial (Неотложная медицинская помощь)
.